Peran Sistem Informasi Akuntansi Penerimaan Kas dalam Optimalisasi Pengendalian Internal (Studi pada PT. GLR) - Rahayu, Duwi (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2025)
This study analyzes the role of the cash receipts accounting information system in optimizing internal controls at PT. GLR, while also assessing the alignment of the company's practices with accounting theory and internal control principles. The research findings are expected to serve as a basis for evaluating and recommending system improvements. A qualitative method was employed, with data collected through interviews, documentation, and observation. Data validity was tested using technique triangulation, while data analysis involved reduction, presentation, and conclusion drawing. The results reveal that the cash receipts accounting information system at PT. GLR is not yet optimal due to the lack of a clear flow diagram. Additionally, internal controls remain weak, particularly in the organizational structure, where there is a gap between administrative and financial functions that needs to be addressed to enhance efficiency and accountability.